INTERPRETING ENTREPRENEURIAL BEHAVIORAL ACCOUNTING FROM THE INDONESIAN CULTURE - Whedy Prasetyo (Center for Indonesian Accounting Studies, 2025)
Research Objective: This study explores the importance of financial reporting for MSMEs from a personality psychology perspective, emphasizing its role in economic decision-making and encouraging the adoption of FAS-MSME to improve the quality of financial information and entrepreneurial decision-making. Method: This study employs a conceptual and literature-based approach to review existing accounting standards, regulatory guidelines, and psychological perspectives related to entrepreneurial behavior. The analysis focuses on aligning the principles of FAS-MSME with the characteristics, needs, and behavioral tendencies of MSMEs. Findings: This study highlights that the complexity of conventional accounting standards often discourages MSMEs from preparing accurate financial statements. FAS-MSME provides a simpler and more relevant framework that matches MSME capacities. When combined with an understanding of personality psychology, MSMEs are more likely to perceive financial reporting not only as compliance but also as a decision-making tool to support growth and sustainability. Theoretical and Policy Implications—This study bridges accounting standardization and behavioral psychology, offering insights into how personality traits shape MSME reporting behavior. From a policy perspective, it supports the promotion and dissemination of FAS-MSMEs by government agencies, professional associations, and educational institutions to ensure that MSMEs receive adequate guidance and training to adopt FAS. Research Novelty: This study integrates personality psychology with financial reporting standardization, presenting a behavioral view of MSME adoption of FAS-MSME and framing it as both a technical and a behavioral tool for financial discipline.